Assessing the influence of teachers’ teaching experience and educational qualification on the use of oral tradition in teaching Igbo language in secondary schools in South-East Nigeria - Ndibe, Princess Ngozi (Journal of Language Literature and Arts, 2026)
The declining use of indigenous languages among younger generations and the increasing reliance on textbook-based instruction have raised concerns about the sustainability of the Igbo language and its cultural heritage. This study examined the influence of teacher-related factors on the integration of oral tradition in Igbo language instruction at the secondary school level. A descriptive survey design was employed. The population comprised public secondary school Igbo language teachers, from which 500 respondents were selected using multistage sampling techniques. Data were collected using a validated questionnaire, and reliability was established through Cronbach’s alpha coefficient. Data analysis involved mean, standard deviation, and analysis of variance (ANOVA) using SPSS, with hypotheses tested at the 0.05 level of significance. The findings revealed a moderate level of oral tradition integration in Igbo language teaching. Folktales, storytelling, songs, and chants were more frequently utilized than proverbs and student-centered practice activities. Educational qualification significantly influenced teachers’ integration of oral tradition, whereas teaching experience showed no significant effect. Teachers generally perceived oral tradition as effective in enhancing students’ interest, retention, confidence, and academic performance, although its contribution to vocabulary development was comparatively lower. Major challenges identified included time constraints, inadequate curricular support, resource demands, and limited student interest. The study concludes that strengthening teacher training and continuous professional development is essential for enhancing the integration of oral tradition in Igbo language instruction, thereby supporting cultural preservation and improving learning outcomes.